Exploring the effects of primordial non-Gaussianity at galactic scales. Issue 1 (1st January 2023) - Stahl, Clément; Montandon, Thomas; Famaey, Benoit; Hahn, Oliver; Ibata, Rodrigo
Abstract: While large scale primordial non-Gaussianity is strongly constrained by present-day data, there are no such constraints at Mpc scales. Here we investigate the effect of significant small-scale primordial non-Gaussianity on structure formation and the galaxy formation process with collisionless simulations: specifically, we explore four different types of non-Gaussianities. All of these prescriptions lead to a distinct and potentially detectable feature in the matter power spectrum around the non-linear scale. The feature might have interesting consequences for the S 8 tension. We then show in particular that a negatively-skewed distribution of the potential random field, hence positively skewed in terms of overdensities, with f NL of the order of 1000 at these scales, implies that typical galaxy-sized halos reach half of their present-day mass at an earlier stage and have a quieter merging history at z < 3 than in the Gaussian case. Their environment between 0.5 and 4 virial radii at z = 0 is less dense than in the Gaussian case. This quieter history and less dense environment has potentially interesting consequences in terms of the formation of bulges and bars. Moreover, we show that the two most massive subhalos around their host tend to display an interesting anti-correlation of velocities, indicative of kinematic coherence. All these hints will need to be statistically confirmed in larger-box simulations with scale-dependent non-Gaussian initial conditions, followed by hydrodynamical zoom-in simulations to explore the detailed consequences of small-scale non-Gaussianities on galaxy formation.